The M-fractional improved perturbed nonlinear Schrodinger equation: Optical solitons and modulation instability analysis - Khalil, Eied M.; Sulaiman, T. A.; Yusuf, Abdullahi; İnç, Mustafa (World Scientific Publ Co Pte Ltd, 2021)
In order to obtain some novel analytical solutions for fractional improved nonlinear Schrodinger equation with perturbation, the polynomial expansion, simplest equation and extended sine-Gordon expansion schemes are utilized. A collection of different types of solitons are reported with a physical and important perspective, containing optical dark solitons. The methods reveal the solutions in a structure of rapidly converging series. This research highlights additional important features of the methods being considered. In addition, the modulation instability analysis is carried out to discuss the stability analysis of the solutions reached, and the movement role of the waves is examined, which affirms that all the established solutions are exact and stable.
Keywords: Nonlinear Schrodinger equation; analytical schemes; optical solitons; modulation instability